Obstructive Sleep Apnoea in adult Population in an Urban Area of Delhi, India: A Community-Based Epidemiological Study - Vishal K. Singh; Farzana Islam; Rambha Pathak; Ashok Shah (Preventive Medicine: Research & Reviews, 2025)
Introduction: The objective of this study was to investigate the risk of obstructive sleep apnoea (OSA) and its association with cardiovascular and socio-demographic factors in the adult population of South Delhi, India. Materials and Methods: Employing a community-based cross-sectional design, authors randomly selected 700 participants aged 30–69 years. The STOP-BANG questionnaire served as our screening tool for OSA risk assessment. Results: The findings revealed that 17.4% of participants exhibited intermediate risk, whereas 3.4% were at high risk for OSA. Notably, certain subgroups demonstrated elevated risk: the elderly, males and individuals with hypertension, diabetics and those who were overweight or obese. Conclusion: OSA is alarmingly prevalent in India, necessitating early identification and intervention. The STOP-BANG questionnaire emerges as a valuable tool for identifying undiagnosed cases, potentially improving health outcomes for affected individuals.